Empagliflozin’s cardioenergetic protective effects through PPARα pathway modulation in heart failure - Wei, Hua; Yin, Menghua; Chang, Junshun; Feng, Bo; Zhou, Qin; Li, Xirong; Wu, Ping; Guo, Xiaoshan; Chen, Siyuan; Li, Bao; Li, Sijin (Frontiers in Pharmacology, 2025)
BackgroundHeart failure (HF) pathology is complex and seriously life-threatening. SGLT2 inhibitors, as one of the new quadruple drugs for HF treatment, have a complex mechanism for improving HF. Energy metabolism is one of the important aspects of HF pathology, and the PPARα signaling pathway plays an important role in energy metabolism. Therefore, this study aims to observe changes in the PPARα signal transduction pathway in chronic HF by 18F-FDG MicroPET/CT imaging. Based on the myocardial metabolic imaging of 18F-FDG MicroPET/CT, this study aims to verify the mechanism of SGLT2 inhibitor treatment in rats with HF through the PPARα signal transduction pathway of energy metabolism and provide an imaging diagnostic basis.ResultsIn 18F-FDG PET/CT myocardial metabolic imaging, pretreatment myocardial glucose metabolism rate (MRGlu) levels in the HC group of HF rats were significantly higher than that in the other three groups. Post-treatment, MRGlu and glucose uptake decreased markedly in the empagliflozin (EMPG) group, while no significant changes were observed in the fenofibrate (FF) group. Compared with normal healthy rats, HF model rats showed a significant increase in MRGlu, and the expression of the lipid metabolism pathway proteins (PPARα, RXRα, CPT1α, and CD36) and the energy metabolism pathway proteins (AMPKα and sirt1) were significantly inhibited, while the expression of the glycolytic pathway protein (GLUT4) was enhanced. After 4 weeks of drug treatment in HF model rats, EMPG showed the same lipid metabolism pathway proteins (PPARα, RXRα, and CPT1α) and energy metabolism pathway proteins (AMPKα and sirt1) as FF, but only EMPG showed a significant decrease in MRGlu, inhibition of glycolytic pathway protein (GLUT 4) expression, and decreased cardiac fibrosis in HF rats.ConclusionThis study led to the following conclusions. 1) Rats with HF showed a significant increase in MRGlu compared with healthy rats. 2) Empagliflozin can improve the energy supply efficiency of the heart in rats with chronic HF by inhibiting glucose metabolism and promoting lipid metabolism, thereby ameliorating energy metabolism in chronic HF. 3) 18F-FDG MicroPET/CT can observe the energy metabolism changes of HF, and the MRGlu can provide quantitative data for the changes of HF energy metabolism.